Nuclear in-medium effects on η dynamics in proton–nucleus collisions - Chen, Jie; Feng, Zhao-Qing; Wang, Jian-Song (Nuclear science and techniques, 2016)
The dynamics of the η meson produced in proton-induced nuclear reactions via the decay of N＊（1535）has been investigated within the Lanzhou quantum molecular dynamics transport model.The in-medium modifications of the η production in dense nuclear matter are included in the model,in which an attractive η-nucleon potential is implemented.The impact of the η optical potential on the η dynamics is investigated.It is found that the attractive potential leads to the reduction in high-momentum（kinetic energy） production from the spectra of momentum distributions and inclusive cross sections and increasing the reabsorption process by surrounding nucleons.